Enabling Ultra-High Work Capacity and Scalable Processability of Liquid Crystal Actuators through Densely Entangled Structures - Li, Caicai (Advanced materials (Deerfield Beach, Fla.), 2025)
© 2025 Wiley‐VCH GmbH.